PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU ADIDAS DI SURABAYA - Hamdan Regatama; Siti Aminah (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the influence of brand image and product quality on purchasing decisions for Adidas shoes in Surabaya. The research seeks to identify whether a strong brand perception and consistent product quality contribute to consumers’ tendency to choose Adidas over competing brands. The study also highlights the increasing competition in the footwear industry and the need for Adidas to strengthen its market positioning through brand and product strategies. The research employs a quantitative approach using a survey method. Data were collected from 120 respondents who reside in Surabaya and have purchased Adidas shoes. The measurement of variables was conducted using a Likert-scale questionnaire, and the data were analyzed using Partial Least Squares (PLS-SEM) to test the measurement model and structural model. The validity, reliability, and significance of the indicators and constructs were evaluated through outer loading, composite reliability, AVE, R-square, and hypothesis testing. The results indicate that both brand image and product quality have a positive and significant influence on purchasing decisions. Brand image shows a stronger effect, reflecting the importance of consumer perception and emotional attachment to the brand. Meanwhile, product quality also significantly contributes to purchasing decisions, proving that durability, design, and functional features remain essential considerations for consumers.